Категорії біле та чорне в теорії та практиці архітектурної композиції - Демків, М. В.; Черняєва, В. М. (Видавництво Львівської політехніки, 2016)
Формулюється поняття “категорій білого та чорного” в архітектурі, виділяються композиційні схеми на основі проведеного аналізу колористики архітектурних об’єктів минулого і сьогодення. Розглядається специфіка формотворення композиційних схем білого та чорного. Особливу увагу приділено архітектурним об’єктам кінця ХХ – початку ХХІ ст. та відзначено композиційні особливості білого та чорного в них. Due to their special semantic richness, psychological, philosophical, cultural, ethical and aesthetic significance white and black have been actively used in everyday life and art for many ages. Since “white” is an achromatic color that reflects the maximum amount of light, and “black” is an achromatic color that absorbs the maximum amount of light, they are extreme expressions of the same, and both are identical. In architectural compositions they are represented by categories of white on white, black on black, white on black, and black on white. There is one more category present in practice, where white equals black - the category of white and black. We can say that in the architecture of ancient cultures and civilizations white and black could be frequently found in the wall paintings, specific architectural details could be highlighted with these colors on the facades of houses. They were presented by regular stonework on the facades of churches in the Middle Ages. In the epoch of Renaissance, a common architectural technique was a breaking a light plane with contrasting dark stripes, which compiled a geometric pattern of squares, diamonds, lines, frames, rings (Cathedral of Santa Maria del Fiore in Florence, San Miniato al Monte, the Baptistery of Saint John in Florence, the Chapel of San Galgano in Monte Siena, Sardinia churches and temples in Tuscany). Under the influence of avant-garde art in the twentieth century white and black are becoming the expression of modernity, the integral parts of compositions in certain areas of architecture, such as minimalism, cubism, high-tech, op-art, conceptualism, they act as accents and dominants in the architectural environment of many cities. They could also be found in functionalism, constructivism and suprematism, since they best express simple spatial patterns and shapes, reveal the silhouette and volume of the building, set orientation in space. Shapes of black and white categories are presented in architecture by compositional schemes. The basic geometric shapes that form these compositional schemes are square, triangle, circle and line. Both main and derivative shapes can make the basis of compositional scheme in architectural practice. Moreover, various operations are carried out with the main shape, thus its transformation into derivative one takes place. These operations include: assimilation with another shape, change of plastics, change of proportions, change of twist, change of rhythm, transfer to the grid structure, intersection, comparison, deformation and overlaying. What is more, each shape undergoes not one, but several operations. If we consider the derivative compositional schemes, where a shape-building element is “square”, the basic operations in their creation can be assimilation, transfer to the grid structure and comparison. The rest of the compositional schemes are formed on the basis of their transformation. The most common operations on changing the basic shape of “circle” is assimilation to the line and square, transfer to the grid structure, comparison and conversion. Compositional schemes based on triangle are formed as the result of operations on assimilation to the square and the line, deformation, change of proportions and rhythms, transfer to the grid structure, and comparison. For transformation of the “line” the compositional schemes frequently use such operations as change of direction, plastics, thickness, grid structure formation, change of rhythm. With different ratio of categories of white and black in the compositions of architecture one can generate different perceptions, sense of architecture, which is one of the main tasks of an architect. Using such techniques, without resorting to the unique three-dimensional and constructive solutions, we can distinguish architectural objects from the crowd, create spatial landmarks and harmonize urban environment, make it integral, introduce statics and dynamism, optical illusions able to capture the attention, give an extraordinary, vivid, emotionally-saturated image to the building. One compositional scheme with the use of the defined categories of white and black allows achieving different images of the building. The issue of this relation remains open; its studying will make it possible to show new sides of the white and black categories in the architectural image making.
Categories of white and black in the theory and practice of architectural composition
Keywords: чорний; білий; архітектурна композиція; архітектурна колористика; black; white, architectural composition, architectural coloring; white; architectural composition; architectural coloring; 72